Breakage, slippage and acceptability outcomes of a condom fitted to penile dimensions. Issue 2 (30th October 2007) - Reece, M; Herbenick, D; Sanders, S A; Monahan, P; Temkit, M; Yarber, W L
Abstract : Objective: This study compared failure rates of a standard-sized condom and a condom fitted to a man's penile length and circumference and assessed users' perceptions of condom acceptability and confidence in the efficacy of both condoms. Method: Using an experimental crossover design with Internet-based daily diaries, 820 men who wore at least one of each condom type reported outcomes and perceptions of condoms used during vaginal and anal intercourse events for which they were the insertive partner. Results: Breakage for fitted condoms (0.7%) was significantly less than for standard-sized condoms (1.4%). When assessed by penile dimensions, significantly less breakage of fitted condoms than standard-sized condoms was observed among men in the middle circumference category (12–13 cm) during anal intercourse (1.2% versus 5.6%), men in the larger circumference category (⩾14 cm) during vaginal intercourse (0.6% versus 2.6%), and men in the longer length category (⩾16 cm) for both vaginal (0.5% versus 2.5%) and anal (3.0% versus 9.8%) intercourse. More slippage upon withdrawal after vaginal intercourse occurred with fitted condoms among men in the middle penile length (1.9% versus 0.9%) and circumference (2.2% versus 0.7%) categories. Conclusions: Fitted condoms may be valuable to sexually transmitted infection prevention efforts, particularly for men with larger penile dimensions. That fitted condoms slipped more for some men provides insights into the need for unique educational materials to accompany such products. Findings also highlight the need for participatory approaches between public health, condom manufacturers, and the retail industry to integrate fitted products into our work successfully.